Factors contributing to acute heart failure after a first acute coronary syndrome episode - Khan, Shehla Ashraf; Kothari, Aanshi S.; Shrivatsam, Paidi; Modi, Sagar M.; Narayan, Jagadale Pratik (International Journal of Research in Medical Sciences, 2025)
Background: Factors that speed up the development of acute heart failure (AHF) after acute coronary syndrome (ACS), are understudied in developing country like India. Therefore, this study was aimed to determine the risk factor of heart failure (HF) among the post-ACS patients. Methods: This descriptive cross-sectional study was performed at Government General Hospital (GGH) Srikakulam, Andhra Pradesh, India. 108 patients who were admitted with HF cardiology unit of GGH after ACS from September 2023 to November 2024 were enrolled in the study. An established inclusion and exclusion criteria along with consecutive sampling technique were used for patients’ recruitment. A self-structured proforma was applied to gather data. Data analysis was done in the statistical package for the social sciences (SPSS) version 25.0. Results: Clinical features, including glucose levels, dyslipidemia, COPD, and medication history, were analyzed in patients with and without ACS. HF was more common in those aged≥40 years (69.23%), male (62.82%), and with anterior wall myocardial infarction (38.46%). Key risk factors included reduced ejection fraction (67.90%), left anterior descending artery pathology (17.95%), absence of myocardial revascularization (46.15%), diabetes mellitus (52.56%), hypertension (78.20%), anemia (53.85%), hyperlipidemia (75.64%), and smoking history (51.28%). Additionally, glucose dysregulation, dyslipidemia, COPD, and medication history influenced HF progression. Conclusions: Factors such as an age group with 40 years or above, male gender, anterior wall myocardial infarction, reduced ejection fraction, left anterior descending artery pathology, absence of myocardial revascularization procedure, diabetes mellitus, hypertension, anemia, hyperlipidemia, and history of smoking, all accelerate the development of HF among post-ACS patients.